Interconnection of the Caper E-Motion System as a Guarantee of Protection of Women's and Children's Rights After Divorce in the Religious Courts of Bengkulu, Indonesia - Asrori, Asrori; Mukhtar, Naqiyah; Wijayati, Mufliha; el-Hajjami, Aicha (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article examines the form of guaranteeing the protection of women's and children's rights after divorce by implementing an application called E-Mosi Caper, namely Electronic Monitoring of the Execution of Financing the Rights of Women and Children after Divorce which is implemented at the Bengkulu Religious Court as a follow-up to the memorandum of agreement between the Religious Courts. Bengkulu with the Bengkulu Bank and the Bengkulu City Government because the ex-husband did not voluntarily implement the decision of the Bengkulu Religious Court regarding these rights, while the ex-wife, due to several obstacles, did not submit an attempt to execute the rights regarding herself and her children. This paper uses a mixed method with a normative juridical and empirical juridical approach. The object of this research is the decision of the Bengkulu Religious Court which has permanent legal force. The primary data sources for this research are the litigants and Bengkulu Religious Court officials. Data collection techniques through observation, interviews and documentation. Inductive data analysis using Maqashid as-Shari'ah theory. The results of the analysis include cases that were decided in 2013, one of the cases was divorce divorce by a husband who worked as an ASN in Bengkulu Province, the ex-wife used this application in February 2023, the result was that as of April 2023, the ex-husband's account was debited in the amount of Rp. 1,000,000/month for his children through his ex-wife's account. The E Mosi Caper application implemented by the Bengkulu Religious Court is an effort to provide excellent service to justice seekers.Keyword: Protection, Rights of Women and Children, Interconnection System.